Genetic Analysis of Pakistani Families Segregating Prelingual Hearing Loss through OtoSeq. (23rd August 2013) - Holle, Jennifer; Sivakumaran, Theru A.; Riazuddin, Sheikh; Friedman, Thomas B.; Riazuddin, Saima; Zhang, Kejian; Ahmed, Zubair M.
Abstract : Objectives: Evaluate the clinical use of OtoSeq, a massive parallel sequencing‐based mutation screening test, in identifying the genetic causes of prelingual hearing loss. Methods: We performed linkage analysis using three fluorescently labeled STR markers for known autosomal recessive nonsyndromic (DFNB) and Usher syndrome (USH) loci on our cohort of Pakistani families segregating prelingual hearing loss. In parallel, we screened one affected individual from some of these families enriched using OtoSeq to identify underlying genetic variants. Sanger sequencing was performed to confirm and study the segregation of identified mutations in each family. For novel mutations, normal hearing individuals from ethnically matched background were screened. Results: Hearing loss in 34 multi‐generational families was found to co‐segregate with USH1B (32 families), USH1D (1 family), and PDS (1 family) linked STR markers. Through OtoSeq, a microdroplet PCR‐based target enrichment followed by MPS, we identified 24 mutations in28 of these families, of which 13 were novel alleles. Sanger sequencing of these mutations showed 100% concordance with MPS data and co‐segregation of the mutant alleles with the hearing loss phenotype in the respective families. Conclusions: The OtoSeq determined the cause of hearing loss in 80% of cases. These results suggest: 1) OtoSeq diagnostic protocol would be a better, cost‐effective, and rapid alternative to current technologies for identifying the multiple genetic causes of hearing loss, and 2) OtoSeq platform should be periodically upgraded to include new deafness genes as they emerge.